Taking over Sokhumi at the beginning XX century (according to Leo Kiacheli’s story "Haki Adzba") - Koberidze, Tamar (Actual Problems of Kartvelology, 2019)
The following article analyzes the history of the Georgians and Apsua-Abkhazian relationship and the history of takeover of Sokhumi by the Soviet Union according to Leo Kiacheli’s ‘ Haki Azba ‘. The author expresses the mainc characters’, Uzush Emkha and his foster-brother – Haki Azba, spiritual attitudes and values very thoroughly, which was shown with the love and century-old respect and brotherhood even in tragic and difficult situation. Such self-sacrifice is completely impossible to understand for the imprudent and having low spiritualness people as well as for the local ruling classes, which shows the essence of the further historical processes in our country.